x2+y2(x−y)2
2y3y2−x2
3x2+y2(2x−y)2
x2+y2(x2−y)
Correct answer is B
x2+y2+xyx+y - x2+y2x−y
= −y3−y3x2−y2
= 2y3x2−y2
= 2y3y2−x2
In ∆PQR. ∠PQR is a right angle. |QR| = 2cm and ∠PRQ = 60o. Find |PR|...
Convert 3.1415926 to 5 decimal places ...
If 2x−3 - 3x−2 = p(x−3)(x−2), find p....
If x varies inversely as y and x=23 when y = 9, find the value of y when \(x=\frac{3}...
This table below gives the scores of a group of students in a Further Mathematics Test. Score...
The angles of a polygon are given by x, 2x, 3x, 4x and 5x respectively. Find the value of x....
Find the value of t in the diagram ...
If P = 18, Q = 21, R = -6 and S = -4, Calculate (P−Q)3+S2R3 ...